School psychologists supporting students with autism through particpation in school based teams - Morton, Jennie Alexis (2022)
Autism Spectrum Disorder, (ASD) is one of the most common neurodevelopmental disorders in the United States with about 1 in 59 children with an ASD diagnosis (Smith et al., 2020). Autism Spectrum Disorder is characterized by recurring deficits in social communication and interaction; and restricted repetitive patterns of behavior, interests, or activities (Smith et al., 2020). Assessing and providing support for individuals with autism within a school can be a challenge for many reasons including comorbid diagnosis with autism, evaluating and implementing interventions, as well as the practitioner’s self-efficacy towards assessing or providing support for students with autism. School professionals may also encounter unique challenges when assessing or supporting a student with autism in an underserved population. Children with low socioeconomic backgrounds, minority groups, or children of parents with less education are most likely to be identified by schools for an evaluation rather than by medical professionals (Zeleke et al., 2019). These families are also more likely to receive assessment, diagnosis, and services through the child’s school compared to private practices (Harris et al., 2019). Therefore, assessment under IDEA (Individuals with Disabilities Education Act) should be provided through a team of different professionals working together to holistically assess and support the individual with autism. The child’s school can be beneficial in evaluating all aspects of the child’s well-being due to engaging in more multidisciplinary team assessment compared to private practice settings (Ward et al., 2016). Based on this information, schools-based teams are needed to support students with autism and students with autism in underserved populations. School Psychologists are important members of school-based teams due to being able to assess autism and comorbid diagnosis in students under IDEA. Although school-based teams are beneficial, there is limited research on how school professionals working with students with autism benefit from team-based services and almost no research on school psychologists specifically. Therefore, are school psychologists effectively assessing and serving students with autism through school-based teams? This thesis will explore four research questions and two exploratory questions to determine how school psychologists can best assess and serve students with autism and students with autism in underserved populations by being a member of a school-based team.